The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/cch.12406
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between self‐ and adult‐perceptions of social competence in children with neuropsychiatric disorders

Abstract: Children's positive self-ratings of social competence relative to adult ratings increased within intervention sample when compared with population sample. The intervention sample children appeared to acknowledge their social competence deficits, yet self-perceptions were inflated relative to adult ratings when focusing on peer relationship difficulties, particularly, aggression to peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
3
5
0
2
Order By: Relevance
“…The results proved that it was not well-fitting for both children’s and parents’ groups, as evidenced by the values of GFC parameters. Similar outcomes were previously reported in the study of Vuori et al 26 (CFI = 0.86 for children’s, CFI = 0.70 for mothers’ and CFI = 0.77 for fathers’ groups). Contrarily, the authors of the scale found this model to be well-fitting in the children’s study group (NNFI = 0.95), but not in the parents’ group due to too high result of SRMR (SRMR = 0.088) 4 .…”
Section: Discussionsupporting
confidence: 90%
“…The results proved that it was not well-fitting for both children’s and parents’ groups, as evidenced by the values of GFC parameters. Similar outcomes were previously reported in the study of Vuori et al 26 (CFI = 0.86 for children’s, CFI = 0.70 for mothers’ and CFI = 0.77 for fathers’ groups). Contrarily, the authors of the scale found this model to be well-fitting in the children’s study group (NNFI = 0.95), but not in the parents’ group due to too high result of SRMR (SRMR = 0.088) 4 .…”
Section: Discussionsupporting
confidence: 90%
“…This suggests response categories typically assumed to represent minor performance difficulties when used by adults, such as ‘A little easy’, may indicate moderate‐to‐significant performance difficulties when selected by young people with developmental disabilities. Additionally, these young people were more likely to select positive rating categories in this and other research, PROMs for young people may need to be sensitive to smaller self‐reported shifts in performance at higher ends of a rating scale, for example from ‘A little easy’ to ‘Very easy’. PROMs for young people with developmental disabilities may also need to include more items assessing the most difficult functional tasks or embed tasks in more difficult contexts, for example talking with strangers instead of familiar people, or concentrating in a very noisy environment.…”
Section: Discussionmentioning
confidence: 75%
“…There is a strong consensus that the assessment of adolescents' psychopathology requires data from multiple informants 1617. Indeed, numerous researchers have reported significant discrepancies between adolescent-reported and parent-reported psychopathology 1819. Although smartphones are widely used and many adolescents have problems related to smartphone use, there is a relative lack of acknowledgement that they can be smartphone addicted 220.…”
Section: Introductionmentioning
confidence: 99%